Physics-chemical properties of water and its natural formation - A E Vorobiev; T V Chekushina; E V Chekushina; A T Roman (RUDN Journal of Engineering Research, 2013)
Were analyzed and compared with each other existing theoretical models of water. In detail the features of the structure of molecules and composition of water for the development of effective methods for the separation of water-soluble gases.